Aromatic compound emissions from municipal solid waste landfill: Emission factors and their impact on air pollution. (August 2016) - Liu, Yanjun; Lu, Wenjing; Guo, Hanwen; Ming, Zhongyuan; Wang, Chi; Xu, Sai; Liu, Yanting; Wang, Hongtao
Abstract: Aromatic compounds (ACs) are major components of volatile organic compounds emitted from municipal solid waste (MSW) landfills. The ACs emissions from the working face of a landfill in Beijing were studied from 2014 to 2015 using a modified wind tunnel system. Emission factors (EFs) of fugitive ACs emissions from the working face of the landfill were proposed according to statistical analyses to cope with their uncertainty. And their impacts on air quality were assessed for the first time. Toluene was the dominant AC with an average emission rate of 38.8 ± 43.0 μg m −2 s −1 (at a sweeping velocity of 0.26 m s −1 ). An increasing trend in AC emission rates was observed from 12:00 to 18:00 and then peaked at 21:00 (314.3 μg m −2 s −1 ). The probability density functions (PDFs) of AC emission rates could be classified into three distributions: Gaussian, log-normal, and logistic. EFs of ACs from the working face of the landfill were proposed according to the 95th percentile cumulative emission rates and the wind effects on ACs emissions. The annual ozone formation and secondary organic aerosol formation potential caused by AC emissions from landfills in Beijing were estimated to be 8.86 × 10 5 kg year −1 and 3.46 × 10 4 kg year −1, respectively. Toluene, m + p -xylene, and 1, 3, 5-trimethylbenzene were the most significant contributors to air pollution. Although ACs pollutions from landfills accounts for less percentage (∼0.1%) compared with other anthropogenic sources, their fugitive emissions which cannot be controlled efficiently deserve more attention and further investigation. Highlights: EFs of ACs from landfill in China were proposed based on statistical analyses. Use PDFs and CDFs to characterize the uncertainty of ACs emission rates. Toluene was the dominant AC with highest emission rate, 38.8 ± 43.0 μg m −2 s −1 . Air pollution caused by AC from landfill is less than other anthropogenic sources.